Hubungan Indeks Massa Tubuh Dengan Tingkat Kejadian Karies Pada Anak Usia 5-12 Tahun : Kajian Pada Pasien Rsgm Fkg Universitas Trisakti (Penelitian) - Gita Cahya Maulani; Jeddy Jeddy (Fakultas Kedokteran Gigi Universitas Trisakti, 2020)
Background: Dental caries is a major health problem affecting most of the world's population and is a multifactorial disease caused by the host, microorganisms, substrate and time. Nutrition is very important in maintaining health, growth, and has a relationship with nutritional status and dental caries. Obesity that occurs in children is a serious and emergency problem because it can last into adulthood. Objective: the aim of this study is to determine the relationship of Body Mass Index with caries incidence rates in children aged 5-12 years. Methods: This study is an observational analytic study with cross-sectional design in children aged 5-12 years at Dental Hospital in Faculty of Dentistry Trisakti University in 2019 with a total sample of 85 children. BMI is measured by weight squared divided by height squared to assess the nutritional status of children, while the def-t index and DMF-T index are used to assess the severity of caries. Results: The incidence rate of deciduous dental caries is very high (def-t index 9.75) and the incidence rate of permanent dental caries is low (DMF-T index 1.27). Data analysis using the Pearson correlation test showed there was no relationship between BMI and the incidence rate of dental caries because the p value was > 0.05. Conclusion: There was no relationship between BMI with caries incidence rates in children aged 5-12 years at Dental Hospital in Faculty of Dentistry Trisakti University.